PENGARUH PAJANAN LOGAM KADMIUM (Cd) TERHADAP KADAR PEROKSIDA (H2O2), KADAR MALODIALDEHID (MDA) DAN KADAR METIL GLIOKSAL (MG) PADA HATI TIKUS PUTIH (Rattus novergicus) - Siti Juliati; Emmy Sri Mahreda; Triawanti Triawanti; Eko Suhartono (EnviroScienteae, 2016)
Cadmium and its compounds are used for various industrial interests. However, the accumulation of cadmium in liver will lead to liver damage. This research aims to analyze the effect of the long exposure of cadmium to wards the levels of H2O2, MDA and MG in white-mouse livers. The number of white-mouse livers used in this research were 24 male mouses which were divided into four treatments of cadmium exposure for zero, two, four and six weeks. After the surgeries, the levels of H2O2, MDA and MG of the white-mouse livers were measured using spectrophotometer UV – VIS. The results showed that there were significant differences in the levels of H2O2 between treatment without exposure to Cd and that exposure. The levels of H2O2 increased respectively 3.164 mmol, 11.076 mmol, 16.292 mmol and 31.588 mmol at the weeks of 0, 2, 4, and 6. The results of the Kruskal-Wallis statistical test (p = 0.000; p <0.05), stated that the long exposure of Cd increased significantly the level of H2O2 in the white-mouse livers. The level of MDA of the white-mouse livers also increased consecutively in the week of 0, 2, 4, and 6 as much as 211.5 μM, 230.6 μM, 269.2 μM and 533 μM. The results of the Kruskal-Wallis statistical test (p = 0.000; p <0.05) showed that the Cd exposure could significantly increase the MDA levels in white-mouse livers. This happened because the Cd exposure activated the phagocytic cells to perform respiratory burst resulting in the accumulation of peroxide compounds. The increased Peroxide with Fe metal that existed in the cytoplasm triggered the lipid peroxidation in the membrane producing the MDA compounds. In addition, the results also showed the increased levels of liver MG consecutively in week 0, 2, 4, and 6 as much as 20.039 %, 24.055 %, 27.985 % and 33.87 % . The results of the Kruskal - Wallis statistical test (p = 0.001 ; p < 0.05), showed that the Cd exposure increased significantly the level of MG which was caused by the metal Cd increased the glycation reaction, i.e., the reaction between glucose and proteins to form Amadori product. At the time of the Amadory formation, the formation of 2,3- enediol which was are easily oxidized by the presence of Cd and oxygen to produce MG occurred. It can be concluded that the exposure of heavy metal cadmium (Cd) for 6 weeks may increase the levels of H2O2, MDA and MG